Digital transformation at higher education institutions for the academic year (2020-2021): Departments of College of Administration and Economics, University of Basrah as a model - et. al., Asst. Lect. Arafat Nasser Jassim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the accelerated pace of developments in information, society and the digital economy, it becomes a fact that the digital environment requires the essential skills and competencies in order to achieve professional success. The individual development of any of them requires the availability of infrastructure, human resources and management competencies. Employment of digital transformation in higher education involves not only technology but also adopting new working methods to continue to provide user-focused services in the face of digital change. This is required in order to maintain survival in a competitive environment and to meet the needs of beneficiaries of digital services with digital skills. This research aims at identifying the level of digital transformation in the College of Administration and Economics at University of Basrah. In this research, the analytical approach and questionnaire were applied to collect research data. The study community was represented by the heads of departments, associate dean for scientific and administrative affairs, and the dean. This comprehensive and focus sample was used for being responsible for leadership and decision, and relied on qualifications, scientific level, position and years of service.